Attracting FDI Post Covid-19 by Simplifying Indonesia's Regulatory Framework - Arianto Patunru; Andree Surianta (Center for Indonesian Policy Studies (CIPS), 2020)
Restrictions to control Covid-19 spread have brought international trade and investment to a halt. Global trade is predicted to fall by 13 – 32%, while foreign direct investment (FDI) may sink even deeper by 30% and 40%. With the world headed to recession, economic recovery post COVID-19 depends on resuming, strengthening, and diversifying global trade networks and investment. In our latest policy brief, we assess Indonesia's Omnibus Bill initiative and outline several recommendations to support making Indonesia more attractive to investments that might open Indonesians to more job prospects, and bring innovation and growth to domestic industries.
Keywords: 330; FDI; investment; foreign investment; regulatory framework; ombibus law; omibus bill; ease of doing business; eodb; covid19; post covid19; corona virus; indonesia economy; economy; ANU